Emodin alleviates hypertrophic scar formation by suppressing macrophage polarization and inhibiting the Notch and TGF-β pathways in macrophages - Xia, Zihuan (Braz J Med Biol Res, 2021)
Hypertrophic scar (HS) formation is a common complication that develops after skin injury; however, there are few effective and specific therapeutic approaches for HS. Emodin has previously been reported to inhibit mechanical stress-induced HS inflammation. Here, we investigated the molecular mechanisms underlying the inhibitory effects of emodin on HS formation. First, we conducted in vitro assays that revealed that emodin inhibited M1 and M2 polarization in rat macrophages. We subsequently established a combined rat model of tail HS and dorsal subcutaneous polyvinyl alcohol (PVA) sponge-induced wounds. Rats were treated with emodin or vehicle (DMEM). Tail scar specimens were harvested at 14, 28, and 42 days post-incision and subjected to H&E staining and Masson's trichrome staining. Histopathological analyses confirmed that emodin attenuated HS formation and fibrosis. Macrophages were separated from wound cells collected from the PVA sponge at 3 and 7 days after implantation. Flow cytometry analysis demonstrated that emodin suppressed in vivo macrophage recruitment and polarization at the wound site. Finally, we explored the molecular mechanisms of emodin in modulating macrophage polarization by evaluating the expression levels of selected effectors of the Notch and TGF-β pathways in macrophages isolated from PVA sponges. Western blot and qPCR assays showed that Notch1, Notch4, Hes1, TGF-β, and Smad3 were downregulated in response to emodin treatment. Taken together, our findings suggested that emodin attenuated HS formation and fibrosis by suppressing macrophage polarization, which is associated with the inhibition of the Notch and TGF-β pathways in macrophages.